1989
DOI: 10.1242/dev.106.3.465
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific expression of c-jun and junB during organogenesis in the mouse

Abstract: c-jun and junB are cellular genes related to the viral oncogene v-jun and encode members of the AP-1 transcription factor gene family. These genes have been implicated in the control of the G0/G1 transition in fibroblasts. Here, we have investigated the potential roles of c-jun and junB during fetal growth and organogenesis in the mouse by in situ hybridization analysis of their expression patterns. c-jun expression is detected throughout organogenesis, and transcripts are detected in many tissues, although in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In the late limb bud, the developing joints represent another prominent site of co‐expression of Dkk‐1 and c‐ Jun . Interestingly, the domains of Bmp‐4, Dkk‐1 and c‐ Jun also overlap at other sites in the embryo, including the otic vesicle and branchial arches, where apoptosis plays a pivotal role to elaborate the shape of the corresponding structure (Wilkinson et al ., 1989; Sanz et al ., 1999; data not shown). This indicates that the molecular cascade for Bmp‐triggered apoptosis we propose (see below) is not limited to the developing limb but might be of general relevance during embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…In the late limb bud, the developing joints represent another prominent site of co‐expression of Dkk‐1 and c‐ Jun . Interestingly, the domains of Bmp‐4, Dkk‐1 and c‐ Jun also overlap at other sites in the embryo, including the otic vesicle and branchial arches, where apoptosis plays a pivotal role to elaborate the shape of the corresponding structure (Wilkinson et al ., 1989; Sanz et al ., 1999; data not shown). This indicates that the molecular cascade for Bmp‐triggered apoptosis we propose (see below) is not limited to the developing limb but might be of general relevance during embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of expression of c-jun and c-fos are rapidly elevated by many growth-stimulatory signals (3). Unlike c-fos, however, c-jun and its related genes are known to be expressed to some extent in a wide variety of tissues in a tissueand stage-specific manner without cell growth stimuli (15,18,35,40,41,48). It is thus plausible that the expression of the Jun family proteins differentially affects the function of Maf and MafB proteins.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, c-jun and junB are known to be immediate early genes whose expression is rapidly and transiently induced by cell growth-stimulatory signals (3,41,47), whereas the expression of junD is constitutive and is scarcely affected under the same conditions (15,18,40). In adult tissues and during embryogenesis, these jun family genes are expressed at different sites (15,18,35,40,48). In addition, their protein products have different biochemical and physiological properties.…”
mentioning
confidence: 99%
“… 37 JUN is currently repeated to be involved in the embryonic brain development, cell‐cycle regulation, apoptosis, and axis formation. 38 , 39 , 40 Some studies have reported that the N‐terminal kinase JUN N‐terminal kinases (JNK) of JUN can activate the MAPK signaling pathway to regulate drug sensitivity and tumor resistance. 41 In our study, CUT and TAG sequencing and dual‐luciferase reporter assay demonstrated that Smad3 might inhibit the transcription of JUN which is contrary to the conclusions of some current studies.…”
Section: Discussionmentioning
confidence: 99%
“…JUN is a proto‐oncogene first discovered in the genome of avian sarcoma virus 17(ASV17) 37 . JUN is currently repeated to be involved in the embryonic brain development, cell‐cycle regulation, apoptosis, and axis formation 38–40 . Some studies have reported that the N‐terminal kinase JUN N‐terminal kinases (JNK) of JUN can activate the MAPK signaling pathway to regulate drug sensitivity and tumor resistance 41 .…”
Section: Discussionmentioning
confidence: 99%